Strategi Jurusan Pendidikan Teknik Sipil dan Perencanaan Menghadapi Revolusi Industri 4.0: Studi Kasus di DIY - Arum Dwi Hastutiningsih; Sugiyono Sugiyono; Suyanto Suyanto; Udik Budi Wibowo (Jurnal Pendidikan Teknik Sipil, 2022)
ABSTRACTIndustrial revolution 4.0 has brought about changes in various sectors, one of which is the management pattern applied in the Department of Civil Engineering and Planning Education. This study aims to find out how the Department of Civil Engineering and Planning deals with the impact of the industrial revolution 4.0, as well as analyze the strategies used to optimize productivity to prepare resources that can compete and have digital capabilities according to the standards of the industrial revolution 4.0 through the POAC (Planning, organizing process, Actuating, Controlling). This research uses descriptive qualitative research with an interview and documentation study. The results of the study show that the strategies that have been applied in dealing with the Industrial Revolution 4.0 in the world of education include strategies that are applied to HR management and management of existing infrastructure in the Department of Civil Engineering and Planning Education. The strategies applied to HR Management include further study schemes, individual competency development schemes, and industrial cooperation schemes, while the strategies applied to Facilities and Infrastructure Management include infrastructure development and media that can be used offline and online.Keywords: Civil Engineering, Human Resources Management, Industry Revolution 4.0, Infrastructure Management,ABSTRAKRevolusi industry 4.0 membawa dampak perubahan pada berbagai sector, salah satunya pada pola manajemen yang diterapkan di jurusan Pendidikan Teknik Sipil dan Perencanaan. Penelitian ini bertujuan untuk mengetahui bagaimana Jurusan Pendidikan Teknik Sipil dan Perencanaan menghadapi dampak Revolusi industry 4.0, serta menganalisis strategi yang digunakan untuk mengoptimalkan produktifitas dalam rangka menyiapkan sumber daya yang mampu bersaing serta memiliki kemampuan digital sesuai standar revolusi industry 4.0 melalui proses POAC (Planning, Organizing, Actuating, Controlling). Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan metode wawancara serta studi dokumentasi. Hasil penelitian menunjukkan strategi yang telah diterapkan dalam menghadapi Revolusi Industri 4.0 dalam dunia Pendidikan meliputi strategi yang diterapkan ke dalam manajemen SDM dan manajemen sarana prasarana yang ada dalam jurusan Pendidikan Teknik Sipil dan Perencanaan. Strategi yang diterapkan ke dalam Manajemen SDM meliputi skema studi lanjut, skema pengembangan kompetensi individu, dan skema kerjasama industri, sedangkan strategi yang diterapkan ke dalam Manajemen Sarana dan Prasarana meliputi pengembangan infrastruktur serta media yang dapat digunakan secara offline maupun online.